Gotong – Royong: Bentuk Komunikasi Sosial Antar Umat Beragama di Surakarta dalam Mewujudkan Masyarakat Madani - Estu Widiyowati (Jurnal Ilmu Komunikasi PROGRESSIO, 2023)
The value of mutual cooperation is able to build and strengthen community social relations, solidarity, and mass mobilization to create social change. This article tries to study the role of the value of mutual cooperation in realizing civil society, especially in a community environment that has religious diversity. This study is important to analyze the role of local wisdom to build civil society in the life of religious people. This research uses an interpretive paradigm to examine the way society creates and maintains its social world. The result of this research is that mutual cooperation reflects moral ethics in people's lives, the value of mutual cooperation still has an existence and has the opportunity to continue to experience the development of forms in the life of urban communities, and mutual cooperation is able to build an attitude of tolerance and social integration as the main capital for realizing civil society.